Historická biogeografie ryb čeledi Cichlidae v zoogeografické provincii Usumacinta (Mexiko, Guatemala, Belize) - Dragová, Klára (Jihočeská univerzita, 2011)
Historical biogeography of cichlid fishes within the Usumacinta province (Mexico, Guatemala, and Belize) is reviewed based on newly collected material specifically for this study. Five areas of endemism within the province were recognized using Parsimony analysis of endemicity. Dispersal-Vicariance analysis implemented in S-DIVA suggests only one of them (the Grijalva-Usumacinta) as the ancestral area for the whole fauna. Other areas of endemism within the Usumacinta province were colonized from this area by dispersals. This biogeographic interpretation suggests a long evolution of the richest cichlid fauna in Middle America in the Grijalva-Usumacinta area of endemism in a sympatric context.
Historical biogeography of cichlid fishes in Usumacinta province (Mexico, Guatemala, Belize)
Keywords: biogeography; cichlid fishes; freshwater fishes; Usumacinta province; Middle America; sympatric evolution; PAE; S-DIVA; biogeography; cichlid fishes; freshwater fishes; Usumacinta province; Middle America; sympatric evolution; PAE; S-DIVA